EVALUASI POLA PENIMBUNAN BATUBARA DALAM UPAYA PENCEGAHAN TERJADINYA SWABAKAR PADA AREA ROM STOCKPILE PT DUTA BARA UTAMA, MUARA ENIM - Alfazry Desrinaldi; Suhardiman Gumanti; Ahmad Husni (Pojok Publisher, 2025)
Spontaneous combustion of coal is a serious problem in the ROM stockpile area, which can cause significant losses in terms of both quality and quantity. This study aims to evaluate the coal stockpiling pattern in the ROM stockpile area of ​​PT Duta Bara Utama in an effort to prevent spontaneous combustion. The methods used in this study include field observations, interviews, and measurements of pile dimensions and pile tilt angles. Based on the analysis, the stockpiling pattern applied is a windrow pattern with a layering method, but there are several factors that have the potential to cause spontaneous combustion, such as low rank coal, pile angles ranging from 40°-50°, non-uniform coal grain sizes, and pile sides that do not consider the cardinal direction. Preventive measures that have been implemented include the FIFO (First in First Out) system, the implementation of a maximum stack standard of 6 meters, compaction of each layer of the pile, and regulation of the stack duration. The results of this study are expected to be a reference in managing coal piles safely and efficiently to prevent spontaneous combustion of coal.